2016
DOI: 10.1007/s12529-016-9537-z
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Quality-of-Life, Lifestyle and Adiposity: A Longitudinal Study in Pre-schoolers (Ballabeina Study)

Abstract: Results emphasise the need for testing moderation in the QOL-adiposity relation. An unhealthy diet can be a vulnerability factor and high physical activity a protective factor in QOL-related adiposity. Consequently, QOL and lifestyle should be targeted concurrently in multi-factorial obesity prevention. The environment should be an 'activity encouraging, healthy food zone' that minimises opportunities for stress-induced eating. In addition, appropriate stress coping skills should be acquired.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 60 publications
0
12
0
3
Order By: Relevance
“…Effect sizes from parent-proxy reports in descriptive studies were variable. Although one study found a large association between physical activity and HRQOL (Norris et al, 2010), the remaining studies found non-significant associations (Lim et al, 2014;Jalali-Farahani et al, 2016;Michels et al, 2016). Interestingly, Norris et al (2010) found a large association based on parent-proxy reports but no association between child-reported physical activity and HRQOL.…”
Section: Effect Sizesmentioning
confidence: 98%
“…Effect sizes from parent-proxy reports in descriptive studies were variable. Although one study found a large association between physical activity and HRQOL (Norris et al, 2010), the remaining studies found non-significant associations (Lim et al, 2014;Jalali-Farahani et al, 2016;Michels et al, 2016). Interestingly, Norris et al (2010) found a large association based on parent-proxy reports but no association between child-reported physical activity and HRQOL.…”
Section: Effect Sizesmentioning
confidence: 98%
“…Overweight and obese children are of concern due to health consequences that may present throughout their lives. Specifically, such children are at an increased risk of developing Type II diabetes, hypertension, dyslipidemia, metabolic syndrome, and bone and joint disorders [2][3][4] . Further, they are more likely to suffer from psychological disorders, including low self-esteem, higher rates of anxiety disorders, body image disturbance, and depressive symptoms, as well as cognitive deficits that begin in childhood and continue throughout life [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the habits acquired during childhood often persist over the course of one's life and that approximately 40% of obese children become obese adults, effective strategies to promote pediatric health must be a global priority and should be implemented early in life [10][11][12] . It is clear that improving health habits and lifestyles of children and their families play key roles in preventing obesity 4,13 . However, in order to successfully promote health in childhood, efforts should not only come from families, but also from society in general [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…Eight studies were conducted in Europe (of which three were in the United Kingdom), five in North America, and three in Australia . Nine of the 16 studies were published in or after 2015 . Only one study included children younger than 3 years old …”
Section: Resultsmentioning
confidence: 99%